Energy efficiency in air transportation - Benito, Arturo; Alonso, Gustavo (Butterworth-Heinemann, an imprint of Elsevier, 2018)
Energy Efficiency in Air Transportation explores the relationship between air transportation and energy use, starting with an analysis of air transport energy sources and their potential development. The book examines how different elements of the air transport system make use of energy, with an analysis of various methods for optimizing energy consumption. The book covers the consequences of energy use in terms of economics, environmental impact and sustainable development, with a review of the existing and proposed regulatory measures addressing those factors. Aeronautical and air transport engineers interested in aerial vehicle systems design, as well as public administrators and regulators concerned with energy efficiency or environmental issues in air transport, will benefit greatly from this comprehensive reference, which captures necessary background information along with the newest developments in the field.
Keywords: Aeronautics, Commercial -- Energy conservation.; Airplanes -- Fuel consumption.; Aeronautics, Commercial -- Environmental aspects.; elektronické knihy; electronic books